Maintenance exercises for urinary continence after rehabilitation following radical prostatectomy: Follow‐up study. Issue 1 (21st November 2021) - Terzoni, Stefano; Ferrara, Paolo; Bellati, Giulia; Mora, Cristina; Pinna, Helené; Borelli, Silvia; Destrebecq, Anne
Abstract: In a previous paper, we presented a complete pelvic floor muscle training (PFMT) program; follow‐up data and maintenance exercises for such program have yet to be studied. The role of PFMT for urinary incontinence after radical prostatectomy is known in literature; the rehabilitation program should be tailored to the patient's needs, and should include maintenance exercises upon completion of the rehabilitation program. The aim of this study is to investigate the effects of a maintenance programme of PFMT on urinary incontinence. After rehabilitation with PFMT, described in previous papers, patients with urinary leakages after radical retropubic prostatectomy followed the maintenance program described in this paper in a prospective study. Leakages were assessed after 3, 6, 12 and 18 months from rehabilitation. Two hundred and seventy‐three patients were included; 216 (79.1%) achieved continence at the end of the rehabilitation programme described in the previous paper; the 57 who remained incontinent were significantly older (66 vs. 71 years, p < 0.001). Continence was maintained in 78.7%, 77.3%, 76.9% and 74.4% of the patients surveyed at 3, 6, 12 and 18 months respectively. The maintenance program proposed in this paper illustrates in detail the body positions, the number of contractions and the moments of the day in which the exercises should be performed. The long‐term effects data support the efficacy of this program. Highlights: Pelvic floor muscle training is an effective method for treating urinary incontinence after radical prostatectomy. In a previous paper, we have shown the efficacy of a complete series of exercises. This paper presents the maintenance programme dedicated at supporting continence in the long run, up to 18 months.